Side-effects of topical steroids: A long overdue revisit - Arijit Coondoo; Meghana Phiske; Shyam Verma; Koushik Lahiri (Wolters Kluwer Medknow Publications, 2014)
The introduction of topical steroids (TS) of varying potency have rendered the therapy of inflammatory cutaneous disorders more effective and less time-consuming. However the usefulness of these has become a double edged sword with constantly rising instances of abuse and misuse leading to serious local, systemic and psychological side effects. These side effects occur more with TS of higher potency and on particular areas of the body like face and genitalia.The article reviews the side effects of TS with special mention about peadiatric age group, also includes the measures for preventing the side effects.